Pengaruh Model Pembelajaran Problem Based Instruction terhadap Hasil Belajar Kognitif - Fadhila, Meidha Zulva; jamaludin, Ujang; Bahrudin, Febrian Alwan (AS-SABIQUN, 2024)
The teaching and learning of Pancasila and Civic Education in 8th grade of Madrasah Tsanawiyah (MTsN) 1 serang city tends to be implemented in a teacher-centered manner in terms of learning outcomes, while the students have not yet reached the minimum completion criteria (KKM). Therefore, the author tried to conduct research on the influence of the Problem Based Instruction (PBI) learning model on cognitive learning outcomes for 8th grades of MTs. Negeri 1 Serang city. This research aims to determine the effect of the Problem Based Instruction (PBI) learning model on cognitive learning outcomes in Civics subjects in 8th grade of MTS Negeri 1 Serang City. This research uses a quantitative approach, the experiment method with a sample of class VIII A students as the control class and class VIII B as the experimental class. In the experimental class, learning uses the Problem Based Instruction (PBI) learning model, while in the control class uses the conventional learning model. To measure learning outcomes in both classes, test techniques were used with instruments in the form of multiple-choice questions. Based on the hypothesis test using the Mann Whitney test, the asymp value was obtained. sig (2-taliled) is 0.000. The value of 0.000 is smaller than 0.05 (0.000 < 0.05). This shows that the use of the Problem Based Instruction (PBI) learning model has an influence on the cognitive learning outcomes of Civic Education subjects for 8th grade of MTs 1 Serang City for the year academic of 2023/2024. Thus, it is concluded that "Hypothesis H1 is accepted and H0 is rejected.